A survey of nurses' knowledge of sleep and its role in patient recovery in a hospital context - Pinna, Marisa Paola Maria (Division of Nursing and Midwifery, 2015)
The aim of this study was to determine professional nurses’ knowledge of sleep and the role of sleep in patient recovery, among 83 professional nurses in a private hospital in Cape Town, South Africa. The nurses in this study were mainly found to have a limited knowledge of sleep and the role of sleep in patient recovery in a hospital context.